THE ANALYSIS OF STRUCTURAL CHANGES IN THE METAL TRAIN WHEELS DURING THEIR OPERATION - Vakulenko, I. O.; Gryshchenko, M. A. (Science and Transport Progress, 2008)
Occurrence of destruction of a railroad wheel is caused by formation of the high local stresses produced by the inhomogeneous elastic-plastic deformation due to the cyclic temperature change during and after braking using brake shoes.